Eat to live : the amazing nutrient-rich program for fast and sustained weight loss - Fuhrman, Joel. (New York : Little, Brown and Co., 2011)
Fuhrman offers a highly effective and scientifically proven way to lose weight quickly, with the simple formula of health = nutrients/calories.
Foreword / Mehmet C. Oz -- Introduction -- Digging our graves with forks and knives: the effects of the American diet, part I -- Overfed, yet malnourished: the effects of the American diet, part II -- Phytochemicals: nature's "magic" pills -- The dark side of animal protein -- Nutritional wisdom makes you thin -- Breaking free of food addiction -- Eat to live takes on disease -- Your plan for substantial weight reduction -- Sculpting our future in the kitchen: menu plans and recipes -- Frequently asked questions.
Includes bibliographical references and index.
PBK
Keywords: Weight loss; Reducing diets -- Recipes